POTENSI ETNOBOTANI MASYARAKAT DESA SEKITAR HUTAN (Studi Kasus di Desa Tamanjaya, Kecamatan Sumur, Kabupaten Pandeglang, Banten) - Asmemare, Kartika; Nitibaskara, Tb. Unu; Lidiawati, Ina (Universitas Nusa Bangsa, 2015)
This study aims to determine the potential of ethnobotany encountered around forest communities. The method used in the study is to survey the field. The activities carried out in this study include: interviews and observation. The data were analyzed descriptively. The results showed that people exploit the potential of ethnobotany of the potency of plants around the forest park and used by the community as much as 72 species of 45 families and can be divided into eleven groups of uses, namely medicinal plants (32 types), decorative (1 species), aromatics ( 6 types), food (23 types), fodder (2 types), pesticide plant (3 types), dye (2 types), firewood (5 types), ceremonies (2 types), building materials (4 types) and material straps, webbing and crafts (4 types).